Parameter identification and damage detection using evolutionary programming - Xu, Jianfeng (2008)
This study develops a general approach based on evolutionary programming (EP) as a backcalculation algorithm for structural nondestructive evaluation (NDE). Although EP has been proven to be robust in finding the global optimum, the speed of convergence could be slow for certain problems. This thesis presents an EP algorithm hybridized with local search strategies. Numerical experiments show that the algorithm improves the search efficiency of the traditional EP method without loss of effectiveness in finding the global optimum. The high search efficiency and effectiveness enhance the feasibility and practicality of applying an EP-based backcalculation algorithm for structural NDE.